Hukum Adat Banjar Dalam Legislasi Lokal (Analisis Adat Masyarakat Banjar Dalam Pemanfaatan Sempadan Sungai Perspektif Fikih Dan Peraturan Daerah Kota Banjarmasin) - Ahmad Syahir; Hanafiah, M.; Sukarni, Sukarni; Muhajir, Ahmad (Sharia Journal and Education Center Publishing, 2024)
Abstract The city of Banjarmasin will always be identified with the river as the center of culture and civilization. Since ancient times, residents of Banjarmasin City have lived side by side with rivers. Many community activities are carried out on the river, such as trading, bathing, washing and other activities. The river in Banjarmasin City is also used by residents as a water transportation route. This research aims to analyze the use of river borders by the people of Banjarmasin City from the perspective of jurisprudence and regional regulations of Banjarmasin City. The significance of this research is to enrich the literature, especially the use of river borders from the perspective of jurisprudence and regional regulations. This research uses library research. The results of the study show that the use of river borders is regulated by the fiqh and regional regulations of the City of Banjarmasin. In fiqh, border is defined as harim an-nahar which cannot be owned according to Sharia. Likewise, regional regulations also regulate the use of borders. Keywords: Riparian Zone, Local Legislation, Banjar Custom Abstrak Kota Banjarmasin tidak lepas dari keberadaan sungai sebagai pusat kebudayaan dan peradaban. Sejak jaman dahulu, warga Kota Banjarmasin telah hidup berdampingan dengan Sungai. Banyak aktivitas masyarakat dilakukan di atas sungai, seperti berdagang, mandi, mencuci, dan aktifitas lainnya. Sungai di Kota Banjarmasin juga dimanfaatkan warga sebagai jalur transportasi air. Penelitian ini menganalisis pemanfaatan sempadan sungai oleh masyarakat Kota Banjarmasin dari perspektif fikih dan peraturan daerah Kota Banjarmasin. Tujuan peneilitian ini adalah untuk menambah kahazanah kepustakaan khususnya dalam pemanfaatan sempadan sungai dipandang dari sudut fikih dan peraturan daerah. Penelitian menggunakan studi pustaka atau library research. Dari hasil kajian menunjukkan pemanfaatan sempadan sungai telah diatur oleh fikih dan juga peraturan daerah Kota Banjarmasin. Dalam fkhazanah fikih, sempadan diartikan harim an-nahar yang secara syar’i tidak dapat dimiliki. Demikian halnya dengan peraturan daerah juga telah mengatur pemanfaatan sempadan. Kata Kunci: Sempadan, Legislasi Lokal, Adat Banjar.